The functions \( f \) and \( g \) are integrable and \( \int_{2}^{4} f(x) d x=-3, \int_{2}^{7} f(x) d x=7 \), and \( \int_{2}^{7} g(x) d x=8 \). Use these to complete parts (a) through (f). 7 (Simplify your answer.) c. \( \int_{2}^{7} 9 g(x) d x=72 \) (Simplify your answer.) d. \( \int_{4}^{7} f(x) d x=\square \) (Simplify your answer.)
Real Tutor Solution
Answer
Solution
Reviewed and approved by the UpStudy tutoring team
Mind Expander
To solve for the required integrals, let’s break down the provided information step by step. First, we have \( \int_{2}^{4} f(x) dx = -3 \) and \( \int_{2}^{7} f(x) dx = 7 \). **c.** To find \( \int_{2}^{7} 9 g(x) dx \), we can factor out the constant 9 from the integral: \[ \int_{2}^{7} 9 g(x) dx = 9 \int_{2}^{7} g(x) dx = 9 \cdot 8 = 72. \] So the answer for part c is **72**. **d.** To find \( \int_{4}^{7} f(x) dx \), we can use the property of definite integrals: \[ \int_{4}^{7} f(x) dx = \int_{2}^{7} f(x) dx - \int_{2}^{4} f(x) dx. \] Substituting the known values, we have: \[ \int_{4}^{7} f(x) dx = 7 - (-3) = 7 + 3 = 10. \] Thus, the answer for part d is **10**.